2020
DOI: 10.1097/cmr.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Survival estimation of melanoma patients with brain metastasis using the Melanoma-molGPA score: external validation from a French cohort

Abstract: While immunotherapies and targeted therapies such as BRAF inhibitors have improved the prognosis, BM is still associated with poor outcome and a short survival. Metastatic melanoma patients are a heterogeneous subgroup with variable prognosis. As several prospective clinical trials have addressed the question of optimal therapy for these patients, an accurate validated selection tool is needed. Melanoma molecular graded prognostic assessment (Melanoma-molGPA) is a new prognostic score for BM melanoma patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This makes it difficult to extrapolate results from prospective trials in relation to highly selected patients and strengthens the need of additional local treatment strategies to improve intracranial control even in the era of recent effective systemic treatment. In our study, using prognostic factors from the melanoma-molGPA score, we found comparable survival rates to those previously reported by Sperduto et al, and patients were well balanced according to melanoma molGPA criteria whether they received LT or not [15,20]. So far LT has not been used to define the criteria of the MolGPA score.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This makes it difficult to extrapolate results from prospective trials in relation to highly selected patients and strengthens the need of additional local treatment strategies to improve intracranial control even in the era of recent effective systemic treatment. In our study, using prognostic factors from the melanoma-molGPA score, we found comparable survival rates to those previously reported by Sperduto et al, and patients were well balanced according to melanoma molGPA criteria whether they received LT or not [15,20]. So far LT has not been used to define the criteria of the MolGPA score.…”
Section: Discussionsupporting
confidence: 88%
“…As part of an institutional board-approved study, all consecutive patients treated at the Institut Universitaire du Cancer and CHU de Toulouse, France between May 2014 and December 2017 for newly diagnosed, locally advanced or metastatic melanoma with available tumour status for BRAF mutation were identified by the treatments' database which excluded patients who did not received systemic treatment. Data on demographics, clinical pathology and molecular analyses, including prognostic factors according to the updated melanoma-molGPA score [15,20] were retrospectively extracted from prospectively collected medical records.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…Various factors influencing patients’ prognosis should be considered before making therapeutic decisions in patients with MBM. The prognosis of patients with brain metastases can be estimated and depends on many factors [ 1 , 5 , 6 , 7 , 8 , 9 ]. Among them are histology and molecular profile of a tumor.…”
Section: Introductionmentioning
confidence: 99%